Glycosylation of glyphosate drives residue reduction and herbicide tolerance in rice - Fulai Yang; Yuehua Wang; Wentao Zhou; Chengfeng Xue; Fengshou Dong; Yongquan Zheng; Meng Zhang; Li Chen; Jun Zhang; Xinglu Pan; Ruifeng Yao (Proceedings of the National Academy of Sciences, 2026)
Glyphosate is the most widely used herbicide globally, especially due to the extensive cultivation of genetically modified glyphosate-resistant crops. However, its intensive application has raised public concerns about the risks to food safety and human health. Identifying enzymes capable of metabolizing glyphosate in plants represents an ideal strategy for addressing this issue, but few are known. Here, we identified the rice variety Kitaake with natural tolerance to glyphosate and demonstrated that this tolerance is driven by glyphosate glycosylation metabolism. Seven up-regulated UDP-dependent glycosyltransferase ( UGT ) genes associated with glyphosate tolerance were identified in Kitaake. Molecular-docking analysis indicated that these UGT proteins have moderate binding affinity for glyphosate. Among these, a deletion of an adenine at position –803 in the promoter region of GLYPHOSATE RESPONSIVE GLYCOSYLTRANSFERASE 1 ( GRGT1 ) enhances its expression in Kitaake. GRGT1 localizes to the endoplasmic reticulum and catalyzes glyphosate glycosylation both in vivo and in vitro. Rice lines complemented with GRGT1–GFP rescue the inability of grgt1 knockout mutants to produce glycosylated glyphosate derivatives. Overexpression of GRGT1 in the susceptible Nipponbare cultivar confers glyphosate tolerance by up-regulating glyphosate metabolism to produce glycosylated glyphosate derivatives M329, M331, and M345. This provides a strategy for developing herbicide-tolerant crops, but also offers a potential approach to consequently reduce glyphosate residues in crops.